The man with the boggy head: cranial melioidosis - Kuan, Yeh Chunn; How, Soon Hin; Ng, Teck Han; Abdul Rani, Mohammed Fauzi (Singapore Medical Association, 2010)
Melioidosis is known to cause abscesses in various organs, including the cranium, though less commonly. We present a patient with scalp abscess and subdural empyema that was visible on computed tomography of the brain. The neurosurgical drainage grew Burkholderia pseudomallei. Despite our best effort to treat the patient using parenteral antibiotics and surgical drainage, the patient did not survive.